CONDITIONS OF PEOPLE’S ADAPTATION AND PROTECTION OF PERSONS AND PROPERTY DURING CRISIS MANAGEMENT IN CASE OF NATURAL HAZARDS (Research Bulletins of the Faculty of Economic Sciences, 2021)
Crisis management is unique form of ruling. Being a science of directinginclude such fields of activity as identification, scheduling, projecting organizational units, activation, completion, controlling, managing resources and property and contact with the surrounding area. In the methodology of science we don’t find any answer to the question appropriate to crisis management: who can and should be in office to govern it? There is also a lack of explicit agreements that might solvethe problem concerning what is important about crisis management, which are itspriorities and validities. Ef-forts are made to pinpoint relations between authorities of governmental units, the mili-tary,emergency servicesand rescue units specialized in various branches (in Poland, for example, the subordination of all volunteer emergency services to the national fire bri-gade). The polymodal and polymorphic complexity of appearances and consequences of various natural hazards derives from their unpredictability, suddennessand intensity. Such a broad range of complexities is the cause for informational instability, bearing consequences for the directional sciences (sensu largo) and crisis management (sensu stricte). The semantic variety, „landscape” ofmeanings(multitude of meanings) and their consequences, appearing in case studies concerning crisis management, requires amethodological reflection in the profession of rational action. In this study an analysis of important methodological aspects has beenundertaken, comprising explorations of people’s behaviour when they are exposed to natural hazards and their direct conse-quences as well. The most important results of scientific research concerning the prob-lem of adaptation to natural hazards have been laid down. Types of reactions of individ-uals and groups to existing threats have been depicted. The particular importance of the assignment and source of power and organisation in case of natural hazards has been substantiated. The possibilities of adaptation to natural hazards by people aggrieved by them have been described as well as the methods of its improvement after the disap-pearance of hazards.
Keywords: intervention to crisis, natural hazards, adjustment to hazard, disasters warn-ings, survival behaviour, coordination of behaviour, emotional aftermath, post-traumatic stress disorder